First capture of Micronycteris homezi Pirlot (Chiroptera, Phyllostomidae) in Brazil - Bernard,Enrico (2001)
The first capture of the phyllostomid bat Micronycteris homezi Pirlot, 1867 in Brazil is reported. An adult male was captured in a forest fragment in Alter do Chão, Santarám, Pará State, in May 7th , 1998. A description of the species, previously reported only in Venezuela and French Guiana, is given, as well as the measures of the captured specimen. After this report, the bat fauna of Brazil is composed by 139 species.